Carers for older people with co-morbid cognitive impairment in general hospital: characteristics and psychological well-being - Bradshaw, Lucy E.; Goldberg, Sarah E.; Schneider, Justine M.; Harwood, Rowan H. (Wiley, 2012)
OBJECTIVE: This analysis sought to describe the characteristics and well-being of carers of older people with mental health problems admitted to a general hospital. METHODS: General medical and trauma orthopaedic patients aged 70 years or older admitted to an acute general teaching hospital were screened for mental health problems. Those screened positive, together with a carer, were invited to undergo further assessment with a battery of health status measurements. Carers were interviewed to ascertain strain (caregiver strain index (CSI)), psychological distress (12-item General Health Questionnaire) and quality of life (EQ-5D). RESULTS: We recruited 250 patients to the study, of whom 180 were cognitively impaired and had carers willing to take part. After 6 months, 57 patients (32%) had died, and we followed up 100 carers. Carers' own health, in terms of mobility, usual activities, and anxiety, was poor in a third of cases. At the time of admission, high carer strain was common (42% with CSI ≥ 7), particularly among co-resident carers (55%). High levels of behavioural and psychiatric symptoms at baseline were associated with more carer strain and distress. At follow-up, carer strain and distress had reduced only slightly, with no difference in outcomes for carers of patients who moved from the community to a care home. CONCLUSION: Hospital staff should be alert to sources of carer strain and offer carers practical advice and emotional support. Interventions are required to prevent and manage behavioural and psychiatric symptoms at the time of acute physical illness or to alleviate their effects on carers.